2019
DOI: 10.1111/asj.13211
|View full text |Cite
|
Sign up to set email alerts
|

Net energy content of five fiber‐rich ingredients fed to pregnant sows

Abstract: The present study was conducted to determine the net energy (NE) values and energy efficiency of wheat bran (WB), sugar beet pulp (SBP), corn gluten feed (CGF), soybean hulls (SBH), and defatted rice bran (DFRB) fed to pregnant sows. Thirty‐six multiparous pregnant sows were randomly assigned to six dietary treatments with six replicates per treatment. Each period lasted for 21 days including 14 days for adaptation. On day 15, sows were moved into respiration chambers for heat production (HP) measurement and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
(54 reference statements)
9
11
1
Order By: Relevance
“…In this study, mobilization of BP and BL of sows fed OPT (64 and 377 g/d, respectively) and CON (28 and 106 g/d, respectively) was quantified. Our BP mobilization values are in the range reported by Pedersen et al [17] (i.e., 28 to 64 g/d vs. 20 to 40 g/d) for sows fed CP diets ranging from 146 to 186 g/kg, but those for BL were noticeably lower (i.e., 106 to 377 g/d vs. 800 to 820 g/d). It is unclear whether estimation of BL and BP mobilization by Pedersen et al [18] was associated with water or not.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, mobilization of BP and BL of sows fed OPT (64 and 377 g/d, respectively) and CON (28 and 106 g/d, respectively) was quantified. Our BP mobilization values are in the range reported by Pedersen et al [17] (i.e., 28 to 64 g/d vs. 20 to 40 g/d) for sows fed CP diets ranging from 146 to 186 g/kg, but those for BL were noticeably lower (i.e., 106 to 377 g/d vs. 800 to 820 g/d). It is unclear whether estimation of BL and BP mobilization by Pedersen et al [18] was associated with water or not.…”
Section: Discussionsupporting
confidence: 77%
“…The NE for maintenance was calculated based on fasting heat production of sows fed corn-soybean meal basal diet by Wang et al [17] as follows:…”
Section: Calculationsmentioning
confidence: 99%
“…The high-fiber ingredients used in this experiment were SBP and DFRB, which have a big difference in dietary fiber content [31]. In the present experiment, the components of GE, TDF, IDF, and SDF in SBP and DFRB were within the range of reported content in these feed ingredients [19,31,[43][44][45][46][47][48]. The results showed that a high-fiber ingredient (SBP and DFRB) formulated in diets could decrease the DE, ME, and ATTD of GE and most nutrients, and these results were consistent with previous studies [7][8][9]44,45].…”
Section: Discussionsupporting
confidence: 52%
“…The respiratory quotient (RQ = CO 2 output: O 2 input) values in this study (supplementary Tables 3 and 6) remained close to 1 throughout lactation, indicating that dietary carbohydrates were serving as primary oxidative substrate [34], and that sows were not in severe negative energy balance. A RQ close to 1 was also previously reported at fed state in growing pigs [10,23,35,36], gestating sows [27,37] and lactating sows [12,24,27].…”
Section: Discussionsupporting
confidence: 82%